Monoterpene Α-Pinene Alleviates Diabetic Retinopathy in Rodent Model via Attenuating Hyperglycemia Induced VEGF Signaling - Dong, Xiao; Zhang, Zhanrong (Indian Journal of Pharmaceutical Education and Research, 2018)
Background: Diabetic Retinopathy (DR) has emerged as a significant global health issue that requires urgent and collaborative action to tackle. As the leading causes of preventable blindness, DR predominantly impacts adults in their working years, posing a significant threat to both individual quality of life and global economic productivity. This research work was aimed at assessing the potency of α-Pinene; a miracle compound on ameliorating hyperglycemia induced diabetic retinopathy in rodent model. Materials and Methods: Male Wistar rats were administered with single shot intraperitoneal 60 mg/kg STZ injection to induce diabetes. The rats exhibited glucose levels 250 mg/dL or higher were classified as diabetic rats and were treated with α-Pinene and a group of diabetic rats were treated with standard anti-hyperglycemic drug metformin. The body weight, feed intake was monitored and the HbA1C, blood glucose levels were quantified to analyse the antihyperglycemic effect of α-Pinene. Results: The lipid profile and atherogenic index were quantified to assess the anti-hypercholesteremic effect of α-Pinene. MDA levels, antioxidants and glutathione levels were measured to examine the antioxidant potency of α-Pinene in hyperglycemic condition. Inflammatory triggering molecules NFκB, TNFα and interleukins 6, 1β were quantified to analyse the inflammatory attenuating effect of α-Pinene. The impact of α-Pinene on VEGF, MMP-9 and MCP-1 were analysed to confirm the attenuating effect of α-Pinene against diabetic retinopathy development and progression. BAX and BCL2 proteins were quantified to examine α-Pinene anti-apoptotic potency in hyperglycemic condition. The retinal thickness and the ganglion cell count were measured to confirm the ameliorating potency of α-Pinene against diabetic retinopathy. Our results demonstrated that α-Pinene is a powerful antioxidant with significant anti-diabetic, anti-hypercholesterolemic, inflammatory modulation, and apoptosis inhibiting effects in a rodent model of diabetic retinopathy. Conclusion: It effectively reduced the initiation and advancement of diabetic induced retinal disorder, as confirmed by histopathological analysis of retinal tissue. In conclusion, α-Pinene is a promising compound with diverse pharmacological properties that can help mitigate diabetic induced retinal disorder.
Keywords: Anti-VEGF drug; Diabetic induced retinal disorder; Inflammation; Oxidative stress; Phytocompound; α-Pinene